2013
DOI: 10.1371/journal.pntd.0002234
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Clinically Relevant Non-Tuberculous Mycobacterial Infections in Saudi Arabia

Abstract: BackgroundNon-Tuberculous Mycobacteria (NTM) are emerging around the world due to a higher prevalence of immunosuppressive illness and therapy. Saudi Arabia is not an exception as there have been novel mycobacterial species also identified. In addition, several published case reports from different parts of the country suggest a growing pathogenic potential of NTM. As the first nationwide study, we sought to gain an insight into the species diversity of NTM clinical isolates.Methodology/Principal findingsDurin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 22 publications
8
41
2
Order By: Relevance
“…In addition, 62.1% of the total study subjects were Saudi nationals. This study concluded that Saudi Arabia has an increasing magnitude of true NTM diseases [38].…”
Section: Emergence Of Non-tuberculous Mycobacterial Infections In Saumentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, 62.1% of the total study subjects were Saudi nationals. This study concluded that Saudi Arabia has an increasing magnitude of true NTM diseases [38].…”
Section: Emergence Of Non-tuberculous Mycobacterial Infections In Saumentioning
confidence: 76%
“…Therefore, building a new registry that can be accessed via internet by the respective users in the NTP, particularly for physicians treating patients, is essential and highly recommended. : Nationwide species diversity of non-tuberculous mycobacteria in Saudi Arabia [38] Need for a central referral research laboratory facility…”
Section: Need For a Centralized Advanced Data Registrymentioning
confidence: 99%
See 1 more Smart Citation
“…In a single institution in Israel, among 215 patients identified with pulmonary NTM isolation over 2004–2010, 21% (45/215) were judged to have definite or probable disease, but clinical information was not detailed (61). From various laboratories in Saudi Arabia, a sample of 95 patients with NTM isolation was identified during 2009–2010, including 73 patients with pulmonary isolation, 67% of whom (49/73) were judged to have pulmonary disease but clinical information was not detailed (62). In Oman, over 2006–2007, a random sample of 13 NTM isolates from the Central Public Health Laboratory in Muscat, was selected for case review (63).…”
Section: Middle East and South Asiamentioning
confidence: 99%
“…Following the global trend of NTM prevalence, Saudi Arabia also reports with an increasing numbers of NTM diseases [7, 9]. In 2013, Varghese et al reported in the first national level study a highly diverse population of clinically relevant NTM’s with the potential of causing pulmonary and extra-pulmonary diseases [9].…”
Section: Introductionmentioning
confidence: 99%